Stress Adaptation to the Mental Resilience of Urban and Rural Adolescents in the Jember Regency - Budiman, M.Elyas Arif; Yuhbaba, Zidni Nuris; Suswati, Wahyi Sholehah Erdah (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2023)
Background: The resilience paradigm is based on contemporary views emerging from the fields of psychiatry, psychology, and sociology on how youth can bounce back and survive stressful conditions, trauma and risks in their lives. The stress experienced by adolescents makes it difficult for them to carry out academic activities at school. The purpose of this research is to develop a stress adaptation model for adolescent mental resilience. The research design used an explanatory survey research design.Methods: The sample size in this study was 250 respondents with a perpusive sampling technique. This research uses stratified random sampling. The test used is Partial Least Square (PLS), which is a Structural Equation Modeling (SEM) technique that is able to analyze latent variables, indicator variables and measurement errors directly.Results: The results of this study indicate that the resilience factor consisting of social competence, problem-solving skills, autonomy and a sense of purpose and future has a significant effect on adaptation stress. Adaptation stress has a significant effect on coping mechanisms. Conclusion: The discovery of stress adaptation models for adolescent mental resilience is associated with resilience to help adolescents bounce back from adversity and successfully adapt to the demands of stressful situations. Adolescents who have resilience perceive adversity as a challenge, not as a threat